Molecular detection of Giardia contamination in water bodies in a zoo - Lim, Y. A.; Lai, M. M.; Mahdy, M. A.; Mat Naim, H. R.; Smith, H. V. (Elsevier, 2009)
We used a combined microscopy-molecular approach to determine the occurrence and identities of waterborne Giardia sp. cysts isolated from 18 separate, 10l grab samples collected from a Malaysian zoo. Microscopy revealed that 17 of 18 samples were Giardia cyst positive with concentrations ranging from 1 to 120 cysts/l. Nine (52.9) of the 17 cyst positive samples produced amplicons of which 7 (77.8) could be sequenced. Giardia duodenalis assemblage A (6 of 7) and assemblage B (1 of 7), both infectious to humans, were identified at all sampling sites at the zoo. The presence of human infectious cysts raises public health issues, and their occurrence, abundance and sources should be investigated further. In this zoo setting, our data highlight the importance of incorporating environmental sampling (monitoring) in addition to routine faecal examinations to determine veterinary and public health risks, and water monitoring should be considered for inclusion as a separate element in hazard analysis, as it often has a historical (accumulative) connotation.